2019
DOI: 10.1101/790766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying conservation priorities in a defaunated tropical biodiversity hotspot

Abstract: Aim: Unsustainable hunting is leading to widespread defaunation across the tropics. To 21 mitigate against this threat with limited conservation resources, stakeholders must 22 make decisions on where to focus anti-poaching activities. Identifying priority areas in a 23 robust way allows decision-makers to target areas of conservation importance, 24 therefore maximizing the impact of conservation interventions. 25 Location: Annamite mountains, Vietnam and Laos.26 2 Methods: We conducted systematic landscape-sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 79 publications
1
44
1
Order By: Relevance
“…Recent studies on coleopterans have increased our taxonomic understanding on several groups of beetles (Brancucci et al 2016) while the study here is in particular pointing towards differences in beetle assemblages between forest habitats and the need to better protect less disturbed forests from human exploitation. Logging and generally habitat degradation are major drivers of declines in biodiversity in tropical biodiversity hotspots such as Laos, while unsustainable hunting is increasingly emerging as a major threat especially larger wildlife (Alroy 2017, Tilker et al, 2020. Compared to other countries in the region, Laos has 21% and thus a large area under protection, however, resources of the government to implement this are limited and more international efforts to support this seem warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on coleopterans have increased our taxonomic understanding on several groups of beetles (Brancucci et al 2016) while the study here is in particular pointing towards differences in beetle assemblages between forest habitats and the need to better protect less disturbed forests from human exploitation. Logging and generally habitat degradation are major drivers of declines in biodiversity in tropical biodiversity hotspots such as Laos, while unsustainable hunting is increasingly emerging as a major threat especially larger wildlife (Alroy 2017, Tilker et al, 2020. Compared to other countries in the region, Laos has 21% and thus a large area under protection, however, resources of the government to implement this are limited and more international efforts to support this seem warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For many species of conservation concern, the detection/non-detection surveys underlying estimates of occurrence are the main source of information on their population status, and therefore have a significant role in setting conservation priorities (MacKenzie, 2005;Joseph et al, 2006). They are useful for a wide range of purposes from estimating changes in occurrence to identifying high conservation priority areas (Zipkin et al, 2010;Olea & Mateo-Tomas, 2011;Tilker et al 2020). Occupancy-based diversity profiles are an important contribution to the occupancy toolkit as they allow comparing biodiversity across space and time while accounting for imperfect and varying detection.…”
Section: Discussionmentioning
confidence: 99%
“…We addressed this problem in part by using data from two marker genes. More than half of the species were detected by both markers, and high correlation in species richness and co-inertia of community composition between the datasets suggested that broad ecological inferences would not have been strongly affected had either marker been chosen by itself (Figures 3 and 5 [24] reported that wild mammal species occupancy increased with remoteness and elevation. However, as Gogarten et al [95] have found, camera-trap and fly-iDNA data classify habitats similarly, even when the two monitoring methods detect largely different communities (only 6% to 43% of species were found by both methods in any given location).…”
Section: Using Idna For Biodiversity Monitoringmentioning
confidence: 99%
“…As such, eDNA has great potential to complement camera traps and acoustic recorders [24], while circumventing some of the logistical issues with deployment and/or loss of field equipment, as well as taxonomic bias. Here, we focus on iDNA, which is a subset of eDNA [25], as an emerging sample type for broad taxonomic and spatial biodiversity monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation